Parenting style, proactive personality, and career decision self-efficacy among senior high school students - Melly Preston; Rose Mini Agoes Salim (Universitas Ahmad Dahlan, 2019)
Making a career decision is one of the most complex development tasks faced by high school students who will graduate from school. Students need to believe that they would succeed in their effort to do the necessary tasks during the process of career decision-making. This belief is referred to as a career decision self-efficacy. This study examined the influence of parenting style on career decision self-efficacy through the mediation of proactive personality in senior high school students. A total of 949 participants were involved in this study. Data were collected using Career Decision Self-Efficacy Scale-Short Form, Parental Authority Questionnaire, and Proactive Personality Scale. Data were analyzed using the regression technique with the Macro Process from Hayes. The regression results show that fathers’ and mothers’ authoritative parenting directly affect career decision self-efficacy; fathers’ and mothers’ authoritarian parenting, as well as mother's permissive parenting, affect the career decision self-efficacy only through the mediation of proactive personality. Also, fathers’ permissive parenting did not have a significant effect on career decisions self-efficacy either directly or indirectly through a proactive personality. Therefore parents – both father and mother – need to involve in developing career decision self-efficacy of their children through parenting process, especially authoritative parenting.